Administrative Delicts: A Case Study in Unlawful Municipal Administration - Magnet, Joseph (Revue générale de droit)

(untitled) (Éditions de l’Université d’Ottawa, 1985)
Municipalities are prone to abuses of power by elected officials. The law books overflow with examples of municipal illegality. This threatens the rule of law.Courts require sufficient remedial authority to maintain the rule of law. An adequate remedy would simultaneously correct the illegal situation, deter repetition, compensate those injured, channel public outrage and, in certain cases, allow supervision of corrupt governmental processes or officials.To satisfy these requirements, a new head of liability is needed. Liability in damages should be imposed for intentional jurisdictional excess.The developing doctrine of administrative delict would provide for damages for deliberate and malicious abuse of power. Damages for an intentional or negligent failure of an individual or administrative body to operate within jurisdiction should be available either against the individual in his personal capacity or against the administrative body.Because many of the wrongs suffered as a result of the illegal use of power are intangible, exemplary damages should be readily available in an action for administrative delict. This remedy would also enable the courts to consider deterrence and breach of public trust in assessing the award.It is the responsibility of administrative law to maintain a sense of orderliness in public administration. The theory of administrative delict needs doctrinal nourishment in order to restrain the abuses of authorities imbued with statutory power.